RESPON PETANI TERHADAP PENGENALAN TEKNOLOGI DAN MANAJEMEN PABRIK KELAPA SAWIT MINI - Rahman, A; Ningsih, Rozaina; Fauzia, Gina; Effran, Endy (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2023)
This research is based on the theory of farm household economics developed by Nakajima, modified by incorporating Miller’s concept of household investment. The aim of this study is to determine whether the Nucleus Estate Smallholder (PIR) Project has succeeded in developing farmers’ ability to invest at the household level. The research was conducted in the Sungai Bahar area, involving 100 independent smallholder respondents from the former oil palm PIR project. The collected data were processed descriptively. The findings show that during the middle period up to about two-thirds of the planting cycle, oil palm cultivation with a land area of 2 hectares still generates a surplus between revenue and costs, enabling farmers to make investments. However, after passing that period—entering the final stage of the planting cycle—there is an indication that 2-hectare oil palm farmers are no longer able to set aside income for replanting or other investments. Independent oil palm smallholders from the ex-PIR project who have successfully made investments are proven to be more resilient in maintaining oil palm plantations that have not yet been replanted, due to the availability of alternative sources of income. The findings of this study suggest that in the last phase of the planting cycle, when production decreases and maintenance expenses remain high, smallholder farmers do not have enough cash to replant. This highlights the need for state support (subsidies, soft loans, and revitalization initiatives) to keep smallholder farmers from becoming locked in a cycle of old, unproductive plantations. Furthermore, farmer empowerment programs should include household economic diversification, not simply palm oil output.